The Backlash in Delhi: British Treatment of the Mughal Royal Family following the Indian “Sepoy Mutiny” of 1857 - Islam, Arshad (Routledge Taylor & Francis Group, 2011)
History tells us much about how a war was fought and won. However, it does not offer us the complete picture inasmuch as it is largely silent about the loser in a conflict and those sympathetic to the cause. This phenomenon in historiography can be noticed in the events of 1857 in the history of India. It was a war of independence but it was seen by most historians merely as a “Sepoy mutiny”. It was a war fought by the common people, men and women, soldiers and chieftains alike under the banner of the last Mughal Emperor of India, Bahadur Shah Zafar (reigned 1837–1857). The British branded this widespread uprising as a rebellion against the legal authority and set in motion a reign of terror after they regained power. Women of the Mughal royal family were particularly targeted by the British soldiers and they experienced untold humiliation. Nevertheless, most account of this struggle for freedom have failed to stress or even record the sufferings of the womenfolk including those of the royal family. Similarly, British historians of the events have been reluctant to take note of eyewitness accounts of the harshness of the returning troops. The present study is an attempt to fill this gap in scholarship about an important revolution. Based on contemporary Urdu, Persian, and English sources (noteworthy publications, personal letters, eyewitness accounts, newspaper reports, and biographical references), the study focuses on the sufferings of the women, which were the worst part of this human tragedy.